Hubungan Indeks Massa Tubuh (IMT) Dengan Resiko Jatuh Pada Lansia Di Desa Tegalsiwalan Kecamatan Tegalsiwalan Kabupaten Probolinggo - Riska Riffatul. M, Rizka Yunita, Shinta Wahyusari (CV. Pusdikra Mitra Jaya, 2023)
Elderly is someone who is experiencing the final stage in the development of human life. The risk of falling is one of the problems caused by intrinsic and extrinsic factors. This study aims to analyze the factors that cause the risk of falls in the elderly. This study uses a correlational analytic study design with a cross sectional approach. The population 130 and the sample 98 elderly respondents at risk of falling in Tegalsiwalan Village, Tegalsiwalan who met the inclusion and exclusion criteria, they were taken by purposive sampling. The instruments used were BB and TB observation sheets, Bivariate test data using spearman rank. The results showed that the risk of falling low category was 41 ederly (41,8%), the risk of falling in the medium category was 8 ederly (9,2%), the risk of falling in the high category was 48 ederly (49,0%). Ederly with thin BMI are 32 ederly (32,7%), ederly with normal BMI are 11 ederly (11,2%) and ederly with fat BMI are 48 ederly (49,0%). The results of the relationship between fall risk and Body mass Index (BMI) OR = 0.389 with a significant value of <0.05 BMI, so it can be stated that H1 is accepted, meaning that there is a relationship between the risk of falling and BMI. The higher the BMI, there will be a buildup of changes in the center of mass of the body, therefore it will have an impact on the risk of falling. It is hoped that the elderly will pay more attention to the impact of the risk of falling.